2014
DOI: 10.1007/s00787-014-0546-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting ADHD in school age when using the Strengths and Difficulties Questionnaire in preschool age: a longitudinal general population study, CCC2000

Abstract: Indicated prevention of ADHD may reduce impairment and need of treatment in youth. The Strengths and Difficulties Questionnaire (SDQ) is a brief questionnaire assessing child mental health, reported to be a valid screening instrument for concurrent ADHD. This study aimed to examine the validity of using the SDQ in preschool age to predict ADHD in school age in a longitudinal design. The study population included 2,315 children from the Copenhagen child cohort 2000 with no prior history of clinically diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…The score ranges between 0 (no problems) and 10 (serious problems), and was dichotomized at a cutoff value of 7 points for both the self‐rated and the parent‐rated subscore as a measure of abnormality in line with SDQ standard original three‐band categorization (http://www.sdqinfo.com/py/sdqinfo/c0.py). The SDQ is commonly used to assess hyperactivity and inattention in population‐based studies of ADHD in children and youth 40, 53, 54.…”
Section: Methodsmentioning
confidence: 99%
“…The score ranges between 0 (no problems) and 10 (serious problems), and was dichotomized at a cutoff value of 7 points for both the self‐rated and the parent‐rated subscore as a measure of abnormality in line with SDQ standard original three‐band categorization (http://www.sdqinfo.com/py/sdqinfo/c0.py). The SDQ is commonly used to assess hyperactivity and inattention in population‐based studies of ADHD in children and youth 40, 53, 54.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] We identified 4 studies that included preschoolers and investigated the screening accuracy of the SDQ HI subscale for ADHD. 10,15,19,20 Two community studies (n ¼ 18,232, age range 5-15 years; n ¼ 1341, age 3 years) 15,20 concluded that the parent SDQ HI subscale discriminated well between children with and without ADHD. A longitudinal study (age range 5-7 years) found that HI subscale scores !6 and reported impact by parents and teachers gave about a 20-fold increased risk of subsequent ADHD.…”
mentioning
confidence: 99%
“…A longitudinal study (age range 5-7 years) found that HI subscale scores !6 and reported impact by parents and teachers gave about a 20-fold increased risk of subsequent ADHD. 19 In addition, a clinical study of children aged 3-17 years found that parent SDQ HI ratings for preschoolers had screening ability for ADHD similar to that for older children, but was limited by the inclusion of few preschoolers (n ¼ 31). 10 In schoolchildren, the discriminative property of the SDQ HI subscale has been found to be as strong for teachers as for parents.…”
mentioning
confidence: 99%
“…However, the majority of generic research examining emotional problems in children with SEN have involved cross‐sectional studies of school‐age children that were not screened for co‐morbid learning difficulties (Salomone et al , ). Because children with SEN are thought to often exhibit problems before entering school, it is difficult to ascertain whether dyslexia alone or co‐morbid SEN are responsible for the alleged pre‐school relationship between dyslexia and psychosocial difficulties (Rimvall et al , ). The present study aimed to clarify how dyslexia, in the absence of co‐occurring difficulties, impacts upon the development of psychological well‐being problems upon entering school.…”
mentioning
confidence: 99%